Technological and Regulatory Changes Impact on Bank Failures Following the 2008 Financial Crisis - Trendowski, Joseph; Nair, Anil (Journal of Applied Business and Economics, 2018)
Regulatory changes (GLBA and IBBEA) allowed banks to operate across state lines and consolidate with investment banks, security firms, and insurance companies. Furthermore, banks were in the middle of a transitionary period where many consumers altered their way of conducting business. Consumers were less limited by geographic location and enjoyed greater convenience. This paper examines the 181 US Bank failures that occurred in one calendar year following the 2008 financial crisis. Using survival analysis, banks founded after deregulation experienced lower failure rates as will banks with higher industry concentration and higher environmental munificence.